A new spectropolarimeter for the San Pedro Martir National Observatory. Issue Volume 9:Issue S302(2013) (7th August 2014) - Iñiguez-Garín, E.; Hiriart, D.; Ramirez-Velez, J.; Núñez-Alfonso, J. M.; Herrera, J.; Castro-Chacón, J.
Abstract: We present the design of a stellar spectropolarimeter to measure the magnetic field of point sources. The polarization module interfaces the Boller and Chivens (B&Ch) intermediate-low resolution (R 500 − 4000) spectrograph to the 2.1-m telescope of the San Pedro Martir National Astronomical Observatory in Mexico. The module uses a Savart plate to split the beam into two orthogonal states of polarization and a quarter (half) waveplate to measure circular (linear) polarization. The module is mounted to the telescope and it feeds the spectrograph through a set of four fibers, two for the polarized star images and two for the spectrograph calibration lamp. The instrument will be capable of measuring polarization in spectral lines to determine the longitudinal and transversal fields in magnetic stars.